2003
DOI: 10.1074/jbc.m308124200
|View full text |Cite
|
Sign up to set email alerts
|

EndoPDI, a Novel Protein-disulfide Isomerase-like Protein That Is Preferentially Expressed in Endothelial Cells Acts as a Stress Survival Factor

Abstract: We have identified a novel protein-disulfide isomerase and named it endothelial protein-disulfide isomerase (EndoPDI) because of its high expression in endothelial cells. Isolation of the full-length cDNA showed EndoPDI to be a 48 kDa protein that has three APWCGHC thioredoxin motifs in contrast to the two present in archetypal PDI. Ribonuclease protection and Western analysis has shown that hypoxia induces EndoPDI mRNA and protein expression. In situ hybridization analysis showed that EndoPDI expression is ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 38 publications
6
143
0
5
Order By: Relevance
“…It has been shown that PDI protects cells against apoptosis/death under both normoxic and hypoxic conditions. 38,39 In the present study, we found that P4HB was expressed in the Leydig cells and in all types of germ cells ( Figure 5). TU + LNG treatment resulted in the down-regulation of the expression of P4HB; this might have weakened the protective effect of P4HB against apoptosis that is triggered by exogenous hormone administration.…”
Section: Discussionsupporting
confidence: 62%
“…It has been shown that PDI protects cells against apoptosis/death under both normoxic and hypoxic conditions. 38,39 In the present study, we found that P4HB was expressed in the Leydig cells and in all types of germ cells ( Figure 5). TU + LNG treatment resulted in the down-regulation of the expression of P4HB; this might have weakened the protective effect of P4HB against apoptosis that is triggered by exogenous hormone administration.…”
Section: Discussionsupporting
confidence: 62%
“…Thioredoxin motifs are also present in molecules such as the protein disulphide isomerases and the endothelial specific PDIs. Whereas PDIs protect endothelial cells during both normoxia and hypoxia, EndoPDIs are upregulated and protect during hypoxic stress (Sullivan et al, 2003). Future investigations of potential antiangiogenic mechanisms may involve effects of AW464 on these redox active molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important question to address because of the crucial antithrombotic role played by healthy endothelium. PDI is present inside endothelial cells and is up-regulated under conditions of hypoxia [14][15][16]. Endothelial cells in culture also express PDI on their exofacial surface, and this PDI regulates the adhesive properties of both thrombospondin [17] and of its binding partner integrin αV β3 [18].…”
Section: Introductionmentioning
confidence: 99%